HD‑Zip I subfamily gene expression in soybean subjected to drought - Pereira, Alan Alves; Morales, Aguida Maria Alves Pereira; Borém, Aluízio; Loureiro, Marcelo Ehlers (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to identify candidate genes of the HD‑Zip I transcription factors subfamily that contribute to drought tolerance in soybean. Trifoliate soybean leaves of drought tolerant (Embrapa 48) and susceptible (BR 16) cultivars were evaluated under three levels of drought: absence, moderate (-1.5 MPa), and severe (-3.0 MPa). Promoter analysis indicated the presence of putative cis-regulatory elements related to water stress in the three genes evaluated (GmHB6, GmHB13, and GmHB21). However, there was no specific pattern of distribution associated with the higher drought tolerance of the genotype. By comparative analysis, six cis-regulatory elements potentially involved in the induction of gene expression under drought were identified. Gene GmHB13 was exclusively induced by drought in the tolerant cultivar, and GmHB6 had its expression reduced only in the susceptible cultivar. Gene GmHB21 showed increased expression in both genotypes. Gene GmHB13 is an important element in the regulation of the drought tolerance mechanism in soybean, in the tolerant cultivar Embrapa 48.